Russia before and after Crimea : nationalism and identity 2010-17 - Kolstø, Pål; Blakkisrud, Helge (Edinburgh University Press Ltd, 2018)
Russia's annexation of Crimea in 2014 brought East - West relations to a low. But, by selling the annexation in starkly nationalist terms to grassroots nationalists, Putin's popularity reached record heights. This volume examines the interactions and tensions between state and societal nationalisms before and after the annexation.